2015
DOI: 10.15713/ins.idmjar.25
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the golden proportion and its implications in the esthetic setting of prosthetic teeth in African melanoderm subjects

Abstract: Introduction:The golden proportion is the sharing considered as the most harmonious of a size in two unequal parts. Its numerical value is of 1.618. Several authors demonstrated that anterior teeth dimensions of the Caucasians are based on the golden section and suggest that the esthetic assembly of the prosthetic teeth holds account of it. The present study searched for a correlation between anterior teeth dimensions and the golden proportion in the African melanoderm. Materials and Methods: Our study has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The ratios on the right side was found to be 1.52 for MCI/MLI on the right and 1.46 and 1.78 for left mci/mli and left MLI/MC respectively. Comparison of our MCI/MLI results with the study done by Pesson et al, revealed GP in a higher percentage of our subjects than the Ivorian melanoderms[16]. The re-A.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The ratios on the right side was found to be 1.52 for MCI/MLI on the right and 1.46 and 1.78 for left mci/mli and left MLI/MC respectively. Comparison of our MCI/MLI results with the study done by Pesson et al, revealed GP in a higher percentage of our subjects than the Ivorian melanoderms[16]. The re-A.…”
supporting
confidence: 74%
“…Demographic characteristics of study participants (n = 100). Frechner as quoted by Shillingburg et al, 1998, showed that the rectangles whose proportions meet the golden ratio are more pleasing to the sight [16]. Also, the measurement of the teeth was restricted to only the GP as explained by Levin, 1978 that during a smile only 62% of the width of the lateral incisor is displayed by the canines [7].…”
Section: Results and Analysismentioning
confidence: 99%
“…In reviewing the articles on golden proportion, the methodology in some of the papers stood out. Studies like that conducted by Pesson 37 focused on comparing measured values, using calipers, to the golden proportion proposed by Levin 4 . Although the measurements in Levin's paper were made from embrasure to embrasure, he had stated that his golden proportions were based on perceived width, as viewed from the front, and not measured width.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies found on the golden proportion involved an assessment of how it compared to tooth proportions in different populations and ethnic groups. Studies were found in Asia, 10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Africa, 37 and Europe, [38][39][40] but no studies on the North or South American population were found. In reviewing these articles, 62% of them found that the golden proportion did not exist in their respective populations (Table 2).…”
Section: Golden Proportionmentioning
confidence: 99%
“…Twenty-nine studies analyzed GP through 2D photographs [14,15,17,20,21,25,26,31-33, 37,40-42,45-51,56,58-60,63,64,68], 10 studies used dental casts [16,23,24,30,43,44,[53][54][55]61] while six studies used both methods of assessment [18,19,22,57,62,65]. Six studies performed direct clinical measurements of teeth on patients [35,36,38,39,66,67] and one study reported digital impressions, digital casts, and 2D photograph analysis in their research [52] (Table 2). All included studies [14][15][16][17][18][19][20][21][22][23][24][25][26] were categorized according to their geographical location.…”
Section: General Analysis Of Included Studiesmentioning
confidence: 99%